Search for blocks/addresses/...

Proofgold Asset

asset id
2954cb0c1a2dc7d0fe8733ee88e83611543fc4c2ed9869d801ccd6f08a4d2e75
asset hash
3e95623ccbb72caa0e3d195d95706251cde9337c19da6d6adc285dca5e04912c
bday / block
24866
tx
ae394..
preasset
doc published by Pr5Zc..
Known 75b00.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 x7)))) = x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x2 x7))))
Known 8c4b6.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 x7)))) = x1 x6 (x1 x5 (x1 x3 (x1 x2 (x1 x4 x7))))
Theorem ed3cb.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x4 (x1 x2 (x1 x5 (x1 x8 x3)))))
...

Theorem 892d6.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x4 (x1 x2 (x1 x5 (x1 x8 x3)))))
...

Known 45f87.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 . x0 x2x0 x3x0 x4x0 x5x1 x2 (x1 x3 (x1 x4 x5)) = x1 x3 (x1 x4 (x1 x2 x5))
Known 9594a.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 x7)))) = x1 x6 (x1 x5 (x1 x4 (x1 x2 (x1 x3 x7))))
Theorem ad8ff.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x4 (x1 x2 (x1 x3 (x1 x8 x5)))))
...

Theorem 11e7c.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x4 (x1 x2 (x1 x3 (x1 x8 x5)))))
...

Known babbf.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 x7)))) = x1 x6 (x1 x5 (x1 x4 (x1 x3 (x1 x2 x7))))
Theorem 61c7f.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x4 (x1 x3 (x1 x2 (x1 x8 x5)))))
...

Theorem b530c.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x4 (x1 x3 (x1 x2 (x1 x8 x5)))))
...

Known 33b72.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x4 (x1 x5 (x1 x3 (x1 x2 (x1 x6 x8)))))
Theorem 10379.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x4 (x1 x5 (x1 x8 (x1 x2 x3)))))
...

Theorem ae475.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x4 (x1 x5 (x1 x8 (x1 x2 x3)))))
...

Known 5b962.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 x7)))) = x1 x6 (x1 x4 (x1 x5 (x1 x3 (x1 x2 x7))))
Theorem 5a3ef.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x4 (x1 x5 (x1 x2 (x1 x8 x3)))))
...

Theorem 0f5b8.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x4 (x1 x5 (x1 x2 (x1 x8 x3)))))
...

Known 44b26.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x4 (x1 x6 (x1 x3 (x1 x2 (x1 x5 x8)))))
Theorem 837b1.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x4 (x1 x8 (x1 x5 (x1 x2 x3)))))
...

Theorem e9883.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x4 (x1 x8 (x1 x5 (x1 x2 x3)))))
...

Known 41caa.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x4 (x1 x3 (x1 x2 (x1 x5 x8)))))
Theorem 7b89f.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x4 (x1 x8 (x1 x3 (x1 x2 x5)))))
...

Theorem a0991.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x4 (x1 x8 (x1 x3 (x1 x2 x5)))))
...

Known a685e.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x6 (x1 x5 (x1 x4 (x1 x7 (x1 x2 (x1 x3 x8)))))
Theorem 09fd3.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x4 (x1 x8 (x1 x2 (x1 x3 x5)))))
...

Theorem 5021b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x4 (x1 x8 (x1 x2 (x1 x3 x5)))))
...

Known 128f2.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x6 (x1 x4 (x1 x7 (x1 x3 (x1 x2 (x1 x5 x8)))))
Theorem acf63.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x4 (x1 x8 (x1 x2 (x1 x5 x3)))))
...

Theorem dc62f.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x4 (x1 x8 (x1 x2 (x1 x5 x3)))))
...

Known c9ff9.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x6 (x1 x5 (x1 x3 (x1 x2 (x1 x7 (x1 x4 x8)))))
Theorem e08e0.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x3 (x1 x2 (x1 x8 (x1 x4 x5)))))
...

Theorem 9898f.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x3 (x1 x2 (x1 x8 (x1 x4 x5)))))
...

Known 93eac.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 . x0 x2x0 x3x0 x4x0 x5x0 x6x1 x2 (x1 x3 (x1 x4 (x1 x5 x6))) = x1 x3 (x1 x4 (x1 x5 (x1 x2 x6)))
Theorem 75428.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x3 (x1 x2 (x1 x8 (x1 x5 x4)))))
...

Theorem 2dc11.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x3 (x1 x2 (x1 x8 (x1 x5 x4)))))
...

Theorem aec73.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x3 (x1 x2 (x1 x5 (x1 x8 x4)))))
...

Theorem 5f90d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x3 (x1 x2 (x1 x5 (x1 x8 x4)))))
...

Theorem 891d7.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x3 (x1 x2 (x1 x4 (x1 x8 x5)))))
...

Theorem 2c899.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x3 (x1 x2 (x1 x4 (x1 x8 x5)))))
...

Theorem 23ca6.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x3 (x1 x4 (x1 x2 (x1 x8 x5)))))
...

Theorem e9a11.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x3 (x1 x4 (x1 x2 (x1 x8 x5)))))
...

Theorem f6da5.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x3 (x1 x5 (x1 x2 (x1 x8 x4)))))
...

Theorem dabc2.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x3 (x1 x5 (x1 x2 (x1 x8 x4)))))
...

Theorem 9c171.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x3 (x1 x8 (x1 x2 (x1 x4 x5)))))
...

Theorem 75edb.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x3 (x1 x8 (x1 x2 (x1 x4 x5)))))
...

Theorem de1d9.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x3 (x1 x8 (x1 x2 (x1 x5 x4)))))
...

Theorem d1abe.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x3 (x1 x8 (x1 x2 (x1 x5 x4)))))
...

Known 809c1.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x6 (x1 x5 (x1 x2 (x1 x3 (x1 x7 (x1 x4 x8)))))
Theorem bfbc2.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x3 (x1 x8 (x1 x4 x5)))))
...

Theorem 70e7d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x3 (x1 x8 (x1 x4 x5)))))
...

Theorem 4bb4f.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x3 (x1 x8 (x1 x5 x4)))))
...

Theorem 6196f.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x3 (x1 x8 (x1 x5 x4)))))
...

Known 76f9e.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 x7)))) = x1 x6 (x1 x5 (x1 x2 (x1 x3 (x1 x4 x7))))
Theorem 3ff1c.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x3 (x1 x5 (x1 x8 x4)))))
...

Theorem 8092f.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x3 (x1 x5 (x1 x8 x4)))))
...

Theorem 3802d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x3 (x1 x4 (x1 x8 x5)))))
...

Theorem 66b9c.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x3 (x1 x4 (x1 x8 x5)))))
...

Known e9e2e.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x6 (x1 x5 (x1 x2 (x1 x4 (x1 x7 (x1 x3 x8)))))
Theorem e8199.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x4 (x1 x8 (x1 x3 x5)))))
...

Theorem f7cac.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x4 (x1 x8 (x1 x3 x5)))))
...

Theorem 1896b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x4 (x1 x8 (x1 x5 x3)))))
...

Theorem a0c55.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x4 (x1 x8 (x1 x5 x3)))))
...

Theorem 771d5.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x4 (x1 x5 (x1 x8 x3)))))
...

Theorem 5a0f8.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x4 (x1 x5 (x1 x8 x3)))))
...

Known 4d854.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 x7)))) = x1 x6 (x1 x5 (x1 x2 (x1 x4 (x1 x3 x7))))
Theorem 3e1be.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x4 (x1 x3 (x1 x8 x5)))))
...

Theorem 4ce15.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x4 (x1 x3 (x1 x8 x5)))))
...

Theorem 89bde.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x5 (x1 x8 (x1 x3 x4)))))
...

Theorem 28d38.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x5 (x1 x8 (x1 x3 x4)))))
...

Theorem 7ccbc.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x5 (x1 x8 (x1 x4 x3)))))
...

Theorem 13816.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x5 (x1 x8 (x1 x4 x3)))))
...

Theorem 9e484.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x5 (x1 x4 (x1 x8 x3)))))
...

Theorem 40a23.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x5 (x1 x4 (x1 x8 x3)))))
...

Theorem 0ce3c.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x5 (x1 x3 (x1 x8 x4)))))
...

Theorem 1db84.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x5 (x1 x3 (x1 x8 x4)))))
...

Known 9492b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x6 (x1 x5 (x1 x2 (x1 x7 (x1 x4 (x1 x3 x8)))))
Theorem dfbdc.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x8 (x1 x5 (x1 x3 x4)))))
...

Theorem f4aed.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x8 (x1 x5 (x1 x3 x4)))))
...

Theorem b8983.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x8 (x1 x5 (x1 x4 x3)))))
...

Theorem 52466.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x8 (x1 x5 (x1 x4 x3)))))
...

Theorem 7fa9f.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x8 (x1 x4 (x1 x3 x5)))))
...

Theorem 4dde1.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x8 (x1 x4 (x1 x3 x5)))))
...

Known 03ffa.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x6 (x1 x5 (x1 x2 (x1 x7 (x1 x3 (x1 x4 x8)))))
Theorem e60f3.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x8 (x1 x4 (x1 x5 x3)))))
...

Theorem 061a7.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x8 (x1 x4 (x1 x5 x3)))))
...

Theorem 95790.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x8 (x1 x3 (x1 x4 x5)))))
...

Theorem 43334.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x8 (x1 x3 (x1 x4 x5)))))
...

Theorem 66393.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x8 (x1 x3 (x1 x5 x4)))))
...

Theorem fbb7f.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x2 (x1 x8 (x1 x3 (x1 x5 x4)))))
...

Known 3d147.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x6 (x1 x7 (x1 x5 (x1 x2 (x1 x4 (x1 x3 x8)))))
Theorem bc311.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x2 (x1 x5 (x1 x3 x4)))))
...

Theorem eb6ae.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x2 (x1 x5 (x1 x3 x4)))))
...

Theorem 7719d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x2 (x1 x5 (x1 x4 x3)))))
...

Theorem 144b9.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x2 (x1 x5 (x1 x4 x3)))))
...

Theorem f1da7.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x2 (x1 x4 (x1 x3 x5)))))
...

Theorem d58a3.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x2 (x1 x4 (x1 x3 x5)))))
...

Known 3805a.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x6 (x1 x7 (x1 x5 (x1 x2 (x1 x3 (x1 x4 x8)))))
Theorem 959f5.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x2 (x1 x4 (x1 x5 x3)))))
...

Theorem 64a00.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x2 (x1 x4 (x1 x5 x3)))))
...

Theorem c126d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x2 (x1 x3 (x1 x4 x5)))))
...

Theorem 12019.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x2 (x1 x3 (x1 x4 x5)))))
...

Theorem 3947b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x2 (x1 x3 (x1 x5 x4)))))
...

Theorem 8ab0b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x2 (x1 x3 (x1 x5 x4)))))
...

Known 5f0b1.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x6 (x1 x5 (x1 x7 (x1 x4 (x1 x2 (x1 x3 x8)))))
Theorem d92ef.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x3 (x1 x2 (x1 x4 x5)))))
...

Theorem 9b07d.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x3 (x1 x2 (x1 x4 x5)))))
...

Theorem 443a6.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x3 (x1 x2 (x1 x5 x4)))))
...

Theorem a8565.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x3 (x1 x2 (x1 x5 x4)))))
...

Known fa965.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x5 (x1 x6 (x1 x4 (x1 x2 (x1 x3 x8)))))
Theorem 668f0.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x4 (x1 x5 (x1 x2 x3)))))
...

Theorem decc1.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x4 (x1 x5 (x1 x2 x3)))))
...

Known 9249b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x6 (x1 x7 (x1 x5 (x1 x4 (x1 x2 (x1 x3 x8)))))
Theorem f22ed.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x4 (x1 x2 (x1 x3 x5)))))
...

Theorem 237ac.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x4 (x1 x2 (x1 x3 x5)))))
...

Theorem a5c16.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x4 (x1 x2 (x1 x5 x3)))))
...

Theorem aabfc.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x4 (x1 x2 (x1 x5 x3)))))
...

Known d6e89.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x6 (x1 x5 (x1 x4 (x1 x2 (x1 x3 x8)))))
Theorem 21736.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x5 (x1 x4 (x1 x2 x3)))))
...

Theorem ef84b.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x5 (x1 x4 (x1 x2 x3)))))
...

Theorem c7d39.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x5 (x1 x2 (x1 x3 x4)))))
...

Theorem f9b59.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x5 (x1 x2 (x1 x3 x4)))))
...

Theorem 8f6a4.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x5 (x1 x2 (x1 x4 x3)))))
...

Theorem 7b0f8.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x6 (x1 x5 (x1 x2 (x1 x4 x3)))))
...

Known 0ab51.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x6 (x1 x7 (x1 x4 (x1 x2 (x1 x5 (x1 x3 x8)))))
Theorem 08108.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x5 (x1 x2 (x1 x6 (x1 x3 x4)))))
...

Theorem d1ff9.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x5 (x1 x2 (x1 x6 (x1 x3 x4)))))
...

Theorem 57f98.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x5 (x1 x2 (x1 x6 (x1 x4 x3)))))
...

Theorem 5bc06.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x5 (x1 x2 (x1 x6 (x1 x4 x3)))))
...

Theorem c6cab.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x5 (x1 x2 (x1 x4 (x1 x3 x6)))))
...

Theorem 7f0f8.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x5 (x1 x2 (x1 x4 (x1 x3 x6)))))
...

Known 7230f.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x6 (x1 x7 (x1 x4 (x1 x2 (x1 x3 (x1 x5 x8)))))
Theorem 67b95.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 x3 (x1 x2 x4))(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x5 (x1 x2 (x1 x4 (x1 x6 x3)))))
...

Theorem cb5ff.. : ∀ x0 : ι → ο . ∀ x1 : ι → ι → ι . (∀ x2 x3 . x0 x2x0 x3x0 (x1 x2 x3))(∀ x2 x3 x4 . x0 x2x0 x3x0 x4x1 x2 (x1 x3 x4) = x1 (x1 x2 x3) x4)(∀ x2 x3 . x0 x2x0 x3x1 x2 x3 = x1 x3 x2)∀ x2 x3 x4 x5 x6 x7 x8 . x0 x2x0 x3x0 x4x0 x5x0 x6x0 x7x0 x8x1 x2 (x1 x3 (x1 x4 (x1 x5 (x1 x6 (x1 x7 x8))))) = x1 x7 (x1 x8 (x1 x5 (x1 x2 (x1 x4 (x1 x6 x3)))))
...